“They know how to navigate… but they don’t know where to go”: Students’ Feedback on Mathematics Teachers’ Practices - L. Jacinto, Everton; Towers, Jo; Martin, Lyndon C. (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
The goal of this paper is to explore aspects of the work of mathematics teachers that students consider problematic and in need of improvement. By using an inductive thematic analysis, we present three themes generated from interviews conducted with 15 students in Alberta, Canada who were participating in high school mathematics upgrading courses. The three themes are: 1) responsiveness, 2) contextualizing the mathematics, and 3) empathy. Our findings show that the majority of the students felt a need for teachers to value the social and emotional dimensions of students’ learning and to listen to students’ concerns rather than adhering to pre-planned or standardized lessons. Students had conflicting views on the extent to which teachers should contextualize the mathematics they are teaching.